ANALISIS OPTIMASI STRUKTUR MODAL PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BEI PERIODE 2019-2023 - Titania Aisyah (Jurnal Bisnis Terapan, 2025)
Optimal capital structure is one of the policies of a company, in which case if the company can optimize its capital structure will have a positive impact on the company's financial performance. Companies that can optimize their capital structure will have an impact on the value of the company, so that it will be an attraction for an investor in investing in the company. Therefore, capital structure is considered important for a company. This study aims to measure the optimal capital structure in Pharmaceutical Sub-Sector Companies Listed on the IDX in 2019 - 2023. The population in this study were Pharmaceutical Sub-Sector Companies Listed on the IDX, using purposive sampling method which finally obtained four companies as samples. This study uses data analysis methods in the form of Capital Structure Composition Ratio, Cost of Capital, Weighted Average Cost of Capital, Tobin's Q Ratio. The results in this study found that in 2021 PT Darya Varia Laboratoria Tbk (DVLA) and in 2019 PT Industri Jamu dan Farmasi Sido Muncul Tbk (SIDO) could maximize their capital structure. And in companies with the code KLBF and PEHA during the five years of observation have not been able to optimize their capital structure.